THE DEVELOPMENT OF ENGLISH READING COMPREHENSION BY USING COOPERATIVE LEARNING STAD TECHNIQUE WITH SQ4R TECHNIQUE FOR GRADE 8 STUDENTS - Sriahmad , Suraiya; Boonprakarn, Kettawa (Journal of MCU Nakhondhat, 2023)
The purpose of this research to develop English Reading Comprehension by Using Cooperative Learning STAD Technique with SQ4R Technique before and after the study of Grade 8 Students. This research is Quasi-experimental research. The researcher designed the quasi-experimental research using the One-Group Pretest-Posttest Design. The sample group in this study was 40 Grade 8 Students in semester 1, the academic Year 2023, at Songserm Wittaya School, Hatyai District, Songkhla Province, which was obtained from Cluster Random sampling because the students in all four classes had good, fair, poor abilities by using the classroom as a random unit. The research instruments were 1) Four lesson plans on The Development of English Reading Comprehension by Using Cooperative Learning STAD Technique with SQ4R Technique for Grade 8 Students three periods per week, total 12 hours. 2) A multiple-choice English Reading Comprehension Test 30 questions. The statistics used for data analysis 1) Basic statistics were percentage, mean, and standard deviation. 2) Statistics used to analyze difficulty, discrimination, and reliability. 3) The statistic used to test hypothesis were t - test dependent. The results found that English Reading Comprehension skill by Using cooperative learning STAD technique with SQ4R technique for Grade 8 Students after learning ( = 20.07, S.D. = 3.58) was higher than before ( = 12.43, S.D. = 3.14) at the statistical significance level of .01.